1990
DOI: 10.1159/000118707
|View full text |Cite
|
Sign up to set email alerts
|

A Multivariate Analysis of Red Blood Cell Membrane Transports and Plasma Levels of <i>L</i>-Tyrosine and <i>L</i>-Tryptophan in Depressed Patients before Treatment and after Clinical Improvement

Abstract: The purpose of this study was to examine whether biological variables, such as erythrocyte membrane transports and plasma levels of monoamine precursor amino acids (tyrosine, tryptophan and phenylalanine), exhibit a particular pattern relatively to DSM-III depressive subgroups (dysthymic disorders, major recurrent depression and biopolar depression), when they are treated synthetically by a stepwise discriminant analysis. We conducted two tests in 97 subjects (64 depressed patients vs. 33 controls): the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
1
5
0
1
Order By: Relevance
“…Plasma TYR and PHE have been measured in the present study, and no change was found between en dogenous depressed patients and normal controls. Moreover, as we showed previously, plasma TYR and PHE levels did not change during a six-week period of drug treatment (Chiaroni et al 1990). Thus, the proba bility that these aminoacids influenced the synthesis of 5-HT is very low, but caution must be taken, as all of the NAAs (i.e., leucine, isoleucine and valine) have not been measured.…”
Section: Discussionsupporting
confidence: 79%
“…Plasma TYR and PHE have been measured in the present study, and no change was found between en dogenous depressed patients and normal controls. Moreover, as we showed previously, plasma TYR and PHE levels did not change during a six-week period of drug treatment (Chiaroni et al 1990). Thus, the proba bility that these aminoacids influenced the synthesis of 5-HT is very low, but caution must be taken, as all of the NAAs (i.e., leucine, isoleucine and valine) have not been measured.…”
Section: Discussionsupporting
confidence: 79%
“…Due to exclusion criteria mentioned in ESF, table 4, three out of these 124 studies were excluded. Hence, the current meta-analysis involved 121 studies (Coppen, Brooksbank et al 1972, Coppen, Eccleston et al 1973, Moller, Kirk et al 1976, Wood, Harwood et al 1978, Shaw, Tidmarsh et al 1980, DeMyer, Shea et al 1981, Healy, Carney et al 1982, Møller, Kirk et al 1982, Menna-Perper 1983, Gerner, Fairbanks et al 1984, Joseph, Brewerton et al 1984, Guicheney, Léger et al 1988, Cowen, Parry-Billings et al 1989, Anderson, Parry-Billings et al 1990, Chiaroni, Azorin et al 1990, Maes, Jacobs et al 1990, Russ, Ackerman et al 1990, Price, Charney et al 1991, Lucca, Lucini et al 1992, Quintana 1992, Maes, Meltzer et al 1993, Møller 1993, Ortiz, Mariscot et al 1993, Karege, Widmer et al 1994, Maes, De Backer et al 1995, Maes, Wauters et al 1996, Maes, Verkerk et al 1997, Mauri, Ferrara et al 1998, Song, Lin et al 1998, Moreno, Gelenberg et al 1999, Hoekstra, van den Broek et al 2001, Mauri, Boscati et al 2001, Porter, Gallagher et al 2003, Rief, Pilger et al 2004, Hayward, Goodwin et al 2005, Hoekstra, Fekkes et al 2006, Miller, Llenos et al 2006, Myint, Kim et al 2007, Myint, Kim et al 2007, Czermak, Hauger et al 2008, Manjarrez-Gutierrez, Marquez et al 2009, Roiser, Levy et al 2009, Gabbay, Klein et al 2010, Olsson, Samuelsson et al 2010, Maes, Galecki et al 2011, Steiner, Walter et al 2011, Sublette, Galfalvy et al 2011, Ebesunun, Eruvulobi et al 2012, Hughes, Carballedo et al 2012, Maes and Rief 2012, Pinto, de Souza et al 2012, Xu, Fang et al 2012, Erhardt, Lim et al 2013, Hennings, Schwarz et al 2013, Moreno, Gaspar et al 2013, Quak, Doornbos et al 2014, Reininghaus, McIntyre et al 2014, Bay-Richter, Linderholm et al 2015, Bradley, Case et al 2015, Busse, Busse et al 2015, Dahl, Andreassen ...…”
Section: Resultsmentioning
confidence: 99%
“…Two CSF studies included both BD-D and BD-M patients ( 29 , 30 ), one solely BD-M ( 31 ) and one solely euthymic BD patients ( 15 ). Eight serum/plasma studies included only BD-D ( 12 , 23 , 33 , 35 37 , 41 , 42 ), one only BD-M ( 14 ), one only euthymic BD ( 39 ), two both BD-D and BD-M patients ( 24 , 40 ), one study both BD-M and euthymic BD ( 34 ) and two studies BD-D, BD-M and BD-Mixed patients ( 10 , 17 ). In the two remaining studies the mood state of BD patients was not specified ( 13 , 38 ).…”
Section: Resultsmentioning
confidence: 99%
“…The quality analysis showed an overall moderate methodological quality with 12 studies (57%) scoring half of the maximum score or more (5/10 or more). Eight studies (38%) had a sample size of less than twenty patients ( 12 , 23 , 29 – 31 , 33 , 36 , 42 ). Only five studies recruited a matched control sample ( 13 , 23 , 24 , 34 , 38 ) and all but one study ( 10 ) reported unadjusted mean TRYCAT levels.…”
Section: Resultsmentioning
confidence: 99%